Training on Creating Interactive Board Media to Enhance Children's Cognitive Development in Distance Learning - Saptarina, Maya Evelyn; Widianto, Edi (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This research aims to help parents overcome challenges in distance learning during the COVID-19 pandemic by training them to create interactive learning boards, enhancing children's cognitive development at home.Method: The study used training sessions for parents to create interactive boards, with feedback collected through surveys based on Donald Kirkpatrick's evaluation model, assessing satisfaction and impact on children's learning.Practical Applications: Parents, equipped with new skills, can now provide more engaging and structured home learning experiences. The interactive boards improved children's focus and cognitive abilities, with 100% of parents recognizing their value.Conclusion: The study reveals that interactive board media created by parents can significantly improve children’s cognitive abilities in distance learning contexts. The high satisfaction rates (93.9%) and the unanimous agreement (100%) on the usefulness of the boards underscore the success of the training. These findings contribute to a broader understanding of how hands-on training for parents can positively impact home-based learning and address educational challenges brought on by the pandemic.